CORPORATE PROFITABILITY LEVEL, CORPORATION MAGNITUDE, AND CORPORATE BOARD MAGNITUDE AS DETERMINANTS OF HOLISTIC EARNINGS MANAGEMENT AMONG LISTED NON-FINANCIAL COMPANIES IN NIGERIA (Journal of Global Accounting, 2023)
Business landscape is becoming increasingly competitive and more intense each day and as such, every company, owners and management strives to better their performance and this has created tendencies geared to realizing a premeditated target through any means possible within the acceptable accounting standards either from real activities or accruals and/or both. This study, as a result, intends to investigate whether corporate profitability level, corporation magnitude, and corporate board magnitude have significant influence on determinants of a holistic earnings management practices among the sampled non financial firms for years 2011 - 2021. Ex-post facto research design was employed and data extracts obtaind were analysed using the multiple regression. Findings made showed that Corporate Profitability level, and Corporate Board Magnitude exert significantly but negative influence on efforts targeted at Holistic Earnings Management (p-values 0.019 and 0.000 < 0.05; z-statistics -1.31 and =3.61 respectively) while Corporation Magnitude does not exert statistically significant influence on efforts targeted at Holistic Earnings Management (p-value 0.295 > 0.05) though it maintained a strong but negative influence (z-statistics -1.05). The study therefore concludes that an increase in corporate profitability level; corporation magnitude; corporate board magnitude and revenue growth leads equivalently to the non-likelihood of sampled firms engaging in holistic earnings management. This implies that where corporate board magnitude is not sufficiently large and equipped to effectively implement management team control, corporate firms already suffering from market capitalization dwindling or fluctuating profitability levels, are exposed to the risk of managing earnings holistically. The study therefore recommends among others that the historical performances of the firms be critically examined especially as it determines the current and future quality of its financial reports.
Keywords: Corporate Board Magnitude; Corporation Magnitude; Corporate Profitability Level; Holistic Earnings Management; Premeditated Targets